Tinjauan Naratif: Efektivitas Nefroprotektif Ekstrak Black garlic (Alium Sativum L.) dalam Menurunkan Kadar Ureum - Wulandari Pramuda Wardani; Intan Adevia Rosnarita; Hasriyani Hasriyani (Universitas Pahlawan Tuanku Tambusai, 2026)
Acute kidney injury can be triggered by gentamicin-induced nephrotoxicity due to drug accumulation in renal cortical epithelial cells, which increases reactive oxygen species (ROS) and causes oxidative stress, as reflected by elevated blood urea levels. Black garlic (Allium sativum L.) contains S-allyl cysteine (SAC), a potent antioxidant that may neutralize oxidative stress and protect the kidney. This narrative review aims to evaluate the effectiveness of black garlic extract in lowering blood urea levels across various animal models of nephrotoxicity. A literature search was conducted on PubMed, Scopus, and Google Scholar for studies published between 2020 and 2025 using the keywords